Post Covid-19 pandemic and the rise of eSports in Malaysia - Chee, Ngee Lim; Salmi Mohd Isa; Ramayah Thurasamy; Norazah Mohd Suki (Penerbit Universiti Kebangsaan Malaysia, 2022)
This conceptual paper explored the COVID-19 pandemic began in early 2020 and rapidly spread to nations due to its strong transmissibility. The Covid-19 pandemic brought about the demise of several businesses, including the sports industry. Thus, the eSports industry has become a feasible alternative and requirement for sporting competitions. This study aims to analyse existing research on the history and growth of eSports in Malaysia to give better insights into its sustainable development, even post-pandemic. This study also covers a detailed assessment of gamers, marketers, and earnings. The study used a literature review strategy and conducted a thorough electronic search for relevant literature using Google Scholar, indexed databases and newspapers. Malaysian governments develop eSports training centres, fund allocations and academies to nurture the athletes and the eSports industry. Many gamers and audiences adapt to the new normal and technologies, particularly during the movement control order. Many Malaysians shift their behaviour and rely on the internet for home entertainment and activities. Covid-19 has enhanced eSports consumption, and the viewership will grow post-pandemic. Game developers invest more money to develop the eSports sector with innovative marketing strategies. This paper focuses on the rise of eSports and the chances for marketers to connect with customers. Many people believe eSports will continue growing, even post-pandemic, as many people have already adapted to it, and cutting-edge technologies also propel many people to accept this unique field.